Growth and carbon relations of mature Picea abies trees under 5 years of free‐air CO2 enrichment. (18th July 2016) - Klein, Tamir; Bader, Martin K.‐F.; Leuzinger, Sebastian; Mildner, Manuel; Schleppi, Patrick; Siegwolf, Rolf T.W.; Körner, Christian
Summary: Are mature forests carbon limited? To explore this question, we exposed ca. 110‐year‐old, 40‐m tall Picea abies trees to a 550‐ppm CO2 concentration in a mixed lowland forest in NW Switzerland. The site receives substantial soluble nitrogen (N) via atmospheric deposition, and thus, trees are unlikely N‐limited. We used a construction crane to operate the free‐air CO2 release system and for canopy access. Here, we summarize the major results for growth and carbon (C) fluxes. Tissue 13 C signals confirmed the effectiveness of the CO2 enrichment system and permitted tracing the continuous flow of new C in trees. Tree responses were individually standardized by pre‐treatment signals. Over the five experimental years, needles retained their photosynthetic capacity and absorbed up to 37% more CO2 under elevated (E) compared to ambient (A) conditions. However, we did not detect an effect on stem radial growth, branch apical growth and needle litter production. Neither stem nor soil CO2 efflux was stimulated under elevated CO2 . The rate at which fine roots filled soil ingrowth cores did not significantly differ between A‐ and E‐trees. Since trees showed no stomatal responses to elevated CO2, sap flow remained unresponsive, both in the long run as well as during short‐term CO2 on–off experiments. As a consequence, soil moisture remained unaffected. We trapped significantly more nitrate in the root sphere of E‐trees suggesting a CO2 ‐stimulated breakdown of soil organic matter, presumably induced by extra carbohydrate exudation ('priming'). Synthesis . The lack of a single enhanced C sink to match the increased C uptake meant a missing C sink. Increased C transport to below‐ground sinks was indicated by C transfer to ectomycorrhiza and on to neighbouring trees and by increased C export to soil. We conclude that these tall Picea abies trees are not C limited at current CO2 concentrations and further atmospheric CO2 enrichment will have at most subtle effects on growth, despite enhanced N availability. Abstract : In a mature mixed forest, 40 m tall spruce trees exposed to 550 ppm CO2 continuously over 5 years showed increased carbon uptake, but no significant increase in growth, nor in respiration. Nevertheless, an increase was observed in carbon transport to belowground sinks: carbon transfer to ectomycorrhiza and on to neighbouring trees, and carbon export to soil. These tall spruce trees are hence not carbon limited at current CO2 concentrations.